Retained austenite phase detected by Mössbauer spectroscopy in ASTM A335 P91 steel submitted to continuous cooling cycles - Jorge I. Besoky; Claudio A. Danon; Cinthia P. Ramos (Journal of Materials Research and Technology, 2019)
Samples of ASTM A335 P91 steel submitted to continuous cooling at different rates were analyzed in the form of foils and powders by means of Mössbauer spectroscopy. The Continuous Cooling Transformation (CCT) diagram of steel ASTM A335 P91 displays two basic microstructural domains at low temperatures – ferritic and martensitic – whose limits depend on the austenite holding temperature, the precise chemical composition and the cooling conditions from the austenite mother phase. Under certain conditions, the martensitic transformation may not be completed, leading to a final microstructure with a non-negligible percentage of the austenite phase retained in a metastable state. This retained austenite could be detrimental for the mechanical properties of the steel.Mössbauer analysis suggested that powdering process promotes the retained austenite transformation to martensite; in particular, in the present case, all the austenite transformed into martensite during powdering. Foil samples instead displayed retained austenite whose relative fraction was determined as a function of the cooling rate. At the same time, the carbon content of retained austenite was estimated for the faster cooled samples; a preliminary explanation for the observed trends is given. Keywords: 9% Cr steel, Martensitic transformation, Retained austenite, Mössbauer spectroscopy